2016
DOI: 10.1371/journal.pone.0146659
|View full text |Cite
|
Sign up to set email alerts
|

Comparisons of Adherence to Antiretroviral Therapy in a High- Risk Population in China: A Systematic Review and Meta-Analysis

Abstract: BackgroundReports on antiretroviral therapy (ART) adherence are scare in China; we performed this meta-analysis to estimate ART adherence rates in different populations at high risk for HIV transmission in China.MethodsWe searched PubMed, Chinese Biomedical Literature Database (Chinese), China National Knowledge Infrastructure (Chinese), and Wanfang (Chinese) to identify studies published from January 1985 to May 2015. We used random-effects meta-analysis to calculate weighted mean estimates across studies and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
15
1
3

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 20 publications
1
15
1
3
Order By: Relevance
“…(2013) in a meta‐analysis of adherence to ART in India (8 studies; 1666 participants), found similar estimates for other low/middle income regions (77%; 95% CI: 68–85; I 2 = 98.4% and 70%; 95% CI: 59–81, I 2 = 96.3% respectively) than that found by our study. Pooled proportion of adherence has also been estimated by other researchers for North America (55%); Spain (55%); worldwide (62%); and for high‐risk subgroups living with HIV such as drug users (60%), pregnant women (73.5%); female sex workers (76%) , adolescents (62%) , prisoners (54.6%) and different high‐risk populations living with HIV in China (77.61%) .…”
Section: Discussionmentioning
confidence: 74%
“…(2013) in a meta‐analysis of adherence to ART in India (8 studies; 1666 participants), found similar estimates for other low/middle income regions (77%; 95% CI: 68–85; I 2 = 98.4% and 70%; 95% CI: 59–81, I 2 = 96.3% respectively) than that found by our study. Pooled proportion of adherence has also been estimated by other researchers for North America (55%); Spain (55%); worldwide (62%); and for high‐risk subgroups living with HIV such as drug users (60%), pregnant women (73.5%); female sex workers (76%) , adolescents (62%) , prisoners (54.6%) and different high‐risk populations living with HIV in China (77.61%) .…”
Section: Discussionmentioning
confidence: 74%
“…However, it was higher than a globally meta-analyzed report (62%) [41], China (77.6%) [30], Africa (77%) [61], India (70%) [29], West Africa (42%) [31]. These discrepancies might be due to the difference in socio-demographic characteristics, healthcare systems, the adherence report method and/or date, study population and study design.…”
Section: Discussionmentioning
confidence: 87%
“…Accordingly, the prevalence of optimal adherence of children to HAART is 90.9% in South India [28], 77% in India [29], 77% in China [30], 42% in West Africa [31] and 76.1% in Nigeria [32]. …”
Section: Introductionmentioning
confidence: 99%
“…A meta-analysis of 111 studies from both developed and developing countries reported an average of 71% of patients had “good” (80% or more doses taken) adherence (95% confidence interval [CI]: 66.0%–75.3%) [4]. In China, recent reports suggest that about 77.6% (95% CI, 71.6%–83.1%) of people living with HIV (PLHIV) on ART report adequate adherence (≥90%) [5]. Although the evidence is somewhat mixed with some reports of 80–90% of MSM reporting adequate adherence [6, 7].…”
Section: Introductionmentioning
confidence: 99%